Frequency of Pattern of Anemia in Chronic Kidney Disease Cases - Alam, Farhad; Abdul Ahad (Indus Journal of Bioscience Research, 2025)
Objective: To determine the frequency of pattern of anemia in chronic kidney disease cases. Methodology: A cross-sectional study was conducted from March to May 2025, including 114 CKD patients. Demographic data, comorbidities, and laboratory parameters (hemoglobin, hematocrit, MCV, MCH, and reticulocyte count) were collected. Anemia was categorized into normochromic, hypochromic, macrocytic, and hemolytic types. Chi-square tests were used to analyze the association between anemia types and comorbidities. Results: Of the 114 patients, 50 (43.9%) had normochromic anemia, 34 (29.8%) had hypochromic anemia, and 15 (13.2%) had both macrocytic and hemolytic anemia. Hypertension was present in 85 (74.6%) and diabetes in 60 (52.6%) patients. A statistically significant relationship between anemia and hypertension was found (p = 0.041), while no significant association was found between anemia and diabetes (p = 0.074). The mean hemoglobin level was 10.2 g/dL, and the mean hematocrit was 33.4%. Conclusion: The study concluded that anemia is highly prevalent in CKD patients, with a significant association between anemia and hypertension. The findings highlight the need for early detection and targeted management of anemia, particularly in hypertensive CKD patients.